Influência da nióbia no óxido de alumínio eletrofundido para aplicações abrasivas - Passos, Edmilson Ricelli dos (Universidade Federal de São Carlos, 2021)
Abrasives are materials that have as main characteristics their cutting and grinding power. In its most common crystalline form, aluminum oxide, due to its high melting point, high hardness and mechanical resistance, is suitable for refractory and abrasive applications. With the increase in the consumption of abrasives and the market's need for more efficient grinding, polishing and cutting tools, this work aimed to verify the influence of niobium oxide on the physical chemical properties of electrofused aluminum oxide. Thus, the work addresses the electrofusion of calcined alumina with the addition of niobia, as well as a comparison of the mechanical properties of this material with emphasis on the abrasive characteristic, comparison with white fused aluminum oxide and brown fused aluminum oxide conventionally found in this market. The samples of the materials obtained were analyzed by X-Ray Diffraction and Fluorescence (DRX and FRX), wear test, instrumented nanohardness, real and bulk density, linear thermal expansion, refractoriness and microstructural characterization by Scan Electron Microscopy coupled to EDS. The results showed that the addition of niobia significantly influenced the increase in the abrasiveness of aluminum oxide, the wear test showed a removal of metallic material 6.6% higher than white fused aluminum oxide and 13.4% higher than brown fused aluminum oxide. Another important influence of the addition of Niobia in aluminum fused oxide was the increase in the thermal expansion coefficient and the reduction in refractoriness. While the white and brown aluminum oxides varied less than 1% of the initial length (at a temperature of 1250°C), the oxide with the addition of niobia presented a variation of 2.78% (at a temperature of 1174.8°C). Thus, it is proven in this work that niobia exerts a great influence on the physicochemical properties of fused aluminum oxides.
Influence of niobia on fused alumina for abrasive applications
Keywords: Alumina eletrofundida; Nióbia; Propriedades mecânicas; Microestrutura; Abrasivos; Fused alumina; Niobia; Mechanical properties; Abrasives; Microstructure; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS